Transformational Leadership, Work Ethic and Quality of Work Life Increase Teachers' Organizational Citizenship Behavior - Abdurahman Tsani, Asep; Gumliar, Aris; Muljadi, M. (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the extent of the influence of transformational leadership, Work Ethic and Quality of Work Life partially and together on Organizational Citizenship Behavior (OCB) of Teachers at SMKN 7 Tangerang Regency. The research method used is associative with a quantitative approach, utilizing moderation regression analysis. The sample consisted of 83 teachers, and the data analysis included multiple regression tests, determination coefficients, and hypothesis significance tests of t-test and F test. Transformal Leadership can project OCB with positive and significant changes to OCB, the higher the Transformal Leadership in SMKN 7 Tangerang Regency can increase OCB. Work Ethic has a positive and significant influence on OCB, as high as the Work Ethic felt by employees can increase Teacher OCB. The Quality of Work Life has a positive and significant influence on the OCB of Teachers, the high quality of Work Life owned by employees can increase OCB, and the Quality of Work Life also has a considerable contribution to the OCB of SMKN 7 Teachers of Tangerang Regency. Quality of Work Life is seen as a very important variable that can affect OCB. By combining transformational leadership, a strong work ethic, and a good quality of work life, schools can create an environment conducive to improving teachers' OCB. This has a positive impact on the effectiveness and efficiency of the overall educational organization.